Hydrogenated Silicon Nitride SiNx:H Deposited by Dielectric Barrier Discharge for Photovoltaics. Issue 1 (16th December 2015) - Massines, Françoise; Silva, José; Lelièvre, Jean‐François; Bazinette, Rémy; Vallade, Julien; Lecouvreur, Paul; Pouliquen, Sylvain
Abstract : Dense hydrogenated silicon nitride (SiNx :H) layers for photovoltaics are made by Atmospheric Pressure Plasma Enhanced Chemical Vapor Deposition (AP‐PECVD). The dependence of morphology, chemical, optical and passivation properties of the thin films on the plasma reactor configuration, the mode of homogeneous DBD (glow, Townsend, RF, nano pulsed) and the SiH4 /NH3 gas flow ratio are investigated. Avoiding gas recirculation, improving thin film homogeneity through the electrode length and the plasma modulation appear as key points. Silicon solar cells made with AP‐PECVD SiN antireflective coating have the same efficiency as standard low pressure PECVD cells, showing the great potential of AP‐PECVD. Abstract : This work demonstrates the great potential of AP‐PECVD SiN x :H films to be applied as antireflective and passivation coating for industrial silicon solar cells. More than the homogeneous DBD mode, it is the modulation of the plasma, the optimization of the gas flow and the optimization of the electrode length that leads to the required density and homogeneity of the film.